Kerja Sama Misionaris dan Perusahaan dalam Pelayanan Kesehatan Masyarakat di Jawa, 1900– 1930 - Fernanda Prasky Hartono; Farabi Fakih (Universitas Gadjah Mada, 2022)
Public health service activities in the Dutch East Indies increased since the early 20th century. Non-governmental organizations have emerged as a new force in providing health services to natives. Two groups that fall into this category are missions and private companies. They were most mentioned for their contribution to public health services in Java. This article aims to look further at the background and form of the relationship between the two groups. The results of this study indicate that cooperation between missions and companies occurs because both are mutually beneficial. In terms of economic benefits and in spreading the influence of each party to society, especially the natives. The relationship between the two is manifested in the form of financial donations and participation in the implementation of new ideas for more effective and efficient health services.